2021
DOI: 10.5194/amt-14-2065-2021
|View full text |Cite
|
Sign up to set email alerts
|

LiSBOA (LiDAR Statistical Barnes Objective Analysis) for optimal design of lidar scans and retrieval of wind statistics – Part 1: Theoretical framework

Abstract: Abstract. A LiDAR Statistical Barnes Objective Analysis (LiSBOA) for the optimal design of lidar scans and retrieval of the velocity statistical moments is proposed. LiSBOA represents an adaptation of the classical Barnes scheme for the statistical analysis of unstructured experimental data in N-dimensional space, and it is a suitable technique for the evaluation over a structured Cartesian grid of the statistics of scalar fields sampled through scanning lidars. LiSBOA is validated and characterized via a Mont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 126 publications
(219 reference statements)
0
15
0
Order By: Relevance
“…An assumption was made to fit the equation to the dual scanning LiDAR system. Previous studies (e.g., Letizia et al 25 ) have indicated that if small elevation angles are used in dual scanning systems, the right‐side third term in Equation (), which associates the vertical velocity component with a sine of the elevation angle can be deleted from the equation. In this experiment, the maximum elevation angle of 6.0° was configured for the measurements at a height of 180 m for SL 1, and sin(6.0°) equals 0.105.…”
Section: Methodsmentioning
confidence: 99%
“…An assumption was made to fit the equation to the dual scanning LiDAR system. Previous studies (e.g., Letizia et al 25 ) have indicated that if small elevation angles are used in dual scanning systems, the right‐side third term in Equation (), which associates the vertical velocity component with a sine of the elevation angle can be deleted from the equation. In this experiment, the maximum elevation angle of 6.0° was configured for the measurements at a height of 180 m for SL 1, and sin(6.0°) equals 0.105.…”
Section: Methodsmentioning
confidence: 99%
“…The scanning strategy for the scanning LiDAR was optimally designed through the LiDAR Statistical Barnes Objective Analysis (LiSBOA) [17] to quantify the hub-height mean velocity with fundamental half-wavelengths of ∆n x = 1D and ∆n y = 0.5D in the streamwise and spanwise directions, respectively, which are deemed to be adequate to spatially resolve flow features of the induction zone and the near-wake (more details available in [18]). With the logistic constraint of the scanning wind LiDAR located 3D upwind of the wind turbines under investigation for the prevailing WSW wind directions, the optimal scan maximizing the coverage of the target volume (70% of the domain adequately sampled) and the statistical convergence (error on the mean of 0.4 m s −1 ) includes 5 planar position indicator (PPI) scans with a range gate of 50 m, elevation angles of the LiDAR laser beam of [3.42 • , 4.39 • , 6.13 • , 10.13 • , 27.95 • ] spanning the azimuthal range [10 • , 100 • ] with a 2 • angular resolution in the azimuthal direction, resulting in a total sampling time of 112 s.…”
Section: Field Experiments To Investigate Rotor-induced Effects On Th...mentioning
confidence: 99%
“…Normalized and clustered data should meet the requirement of statistical homogeneity [4,18], which allows using the LiSBOA tool [17] to reconstruct the low-pass filtered mean velocity fields on a Cartesian grid at hub height. To this aim, the pre-conditioned LiDAR data collected within the vertical range z ∈ (H − D/4, H + D/4) are fed to the LiSBOA algorithm using a smoothing parameter of the Barnes scheme σ = 1/3, and the fundamental half-wavelengths provided in Section 2.…”
Section: (2022) 022033mentioning
confidence: 99%
“…For instance, LiDAR scans can be optimally designed to probe the atmospheric boundary layer and wakes generated by utility-scale wind turbines (e.g. El-Asha, Zhan & Iungo 2017; Zhan, Letizia & Iungo 2020; Letizia, Zhan & Iungo 2021 a , b ). Regarding atmospheric turbulence, LiDAR measurements were used to detect the inverse-power law (Calaf et al.…”
Section: Introductionmentioning
confidence: 99%